The Implementation of Comic Supplementary Tutor Feedback In Contextual Teaching Hybrid Learning on The Achievement of Higher Order Thinking Skill Viewed From Students’ Mathematics Disposition - Guntur, Mochamad; Kartono, Kartono; Junaedi, Iwan (Unnes Journal of Mathematics Education Research, 2021)
This study aims to determine the quality of learning by applying comic supplementary tutor feedback in contextual teaching hybrid learning in order to achieve students' higher order thinking skills in mathematics. The method used in this study is mixed methods with sequential design. The results of this study showed that the implementation of comic supplementary tutor feedback in the contextual teaching hybrid learning had a certain quality on achieving students' higher order thinking skills in mathematics. In subjects with higher category disposition, it revealed that the answers of subject 1 and subject 2 have reached the indicator of analyzing and evaluating, but the indicator of creating has not been seen yet. Moreover, subjects with moderate disposition category showed that the answers of subject 1 and subject 3 have reached the indicator of analyzing and evaluating but the indicators of creating have not been seen yet. Whereas subject 2 showed that indicators of analyzing, evaluating, and creating have not been achieved yet. However, subjects with low category disposition showed that the answers of subject 1 did not show the achievement on the indicator of analyzing, evaluating and creating, but at the evaluating stage, there was already a correct answer until the end